Management Of Sports Education And Training Centers For Running Athlete Students - Haryanto, Arief Ibnu; Suardika, I Kadek; Taidi, Mohamad Djalil; Udjulu, Izrak; Nopiyanto, Yahya Eko; Fatahi, Ali; Muhammad, Noor (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2024)
The aim of this research was to describe the implementation of the management of the Gorontalo Province Student Sports Education and Training Center (PPLP) in the running sport. This research was a quantitative descriptive research using survey methods and data collection techniques which were measured by using questionnaires distributed to respondents. The subjects of this research were all athletes from the Gorontalo Province Student Sports Education and Training Center (PPLP) in running sports (total sampling), totaling ten athletes. The research instrument uses a Likert scale which has a level of validity and reliability of the instrument from previous research and has been tested. As a result, overall the majority of respondents were in the high category in the aspects of planning, organizing, leadership and control. The conclusion is that, due to the high level of management implementation that has occurred, this research plays an important role in increasing understanding of how to manage sports practices, with possible results that can improve and develop sports management in the region.